2005
DOI: 10.1002/ijc.21204
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II allele control of HPV load in carcinoma in situ of the cervix uteri

Abstract: Human papillomavirus (HPV) infection is the most important risk factor for development of cervical carcinoma. Carriers of certain HLA class II alleles, e.g., DRB1*1501 and DQB1*0602, are more prone to HPV 16 infection and cervical carcinoma, whereas other alleles, e.g., DRB1*1301 and DQB1*0603, render carriers less susceptible to the disease. In our study comprising 484 cases and 601 controls, we examine the effect of HLA class II alleles on viral load of the oncogenic types HPV 18/45 and HPV 31 and risk of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…This finds support by the observation that HPV 16 and 18/45 positive carriers of commonly reported protective human histocompatibility leukocyte antigen class II (HLA II) alleles displayed lower viral loads together with short term HPV infections and a decreased risk of cervical carcinoma in situ. 25,26 Although our findings for non-HPV 16 types are in line with some studies, 11 it contradicts others. 12 Variables such as differences in methods to preselect hrHPV positive women 6 and sample size may have contributed to inconsistent data for non-HPV 16 types.…”
Section: Discussionsupporting
confidence: 62%
“…This finds support by the observation that HPV 16 and 18/45 positive carriers of commonly reported protective human histocompatibility leukocyte antigen class II (HLA II) alleles displayed lower viral loads together with short term HPV infections and a decreased risk of cervical carcinoma in situ. 25,26 Although our findings for non-HPV 16 types are in line with some studies, 11 it contradicts others. 12 Variables such as differences in methods to preselect hrHPV positive women 6 and sample size may have contributed to inconsistent data for non-HPV 16 types.…”
Section: Discussionsupporting
confidence: 62%
“…We found a decreased risk of CSCC in association with the HLA-DPB1*05:01 allele and +550 G/G genotype and G allele and an increased risk in association with the +550 A allele. When the analysis was restricted to the subgroup of women with HPV-16 positive CSCC, the association of HLA-DPB1*05:01 allele still existed and the DPB1 Certain HLA class II alleles have been reported to influence cervical cancer development by affecting the interactions between host immune response and HPV infection [23][24][25][26]. The DRB1 and DQB1 loci therefore have been thoroughly investigated in several cervical cancer association studies [5].…”
Section: Discussionmentioning
confidence: 97%
“…A Swedish study reported that DRB1*1301 and DQB1*0603 carriers had a lower HPV18 of 45 titer in comparison to noncarriers. 17 Cohort studies in Brazil and Canada showed inconsistent findings for the association between HLA class II genes and persistent infection. 19,20 In these studies, the average age of participants was 20 to 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…A Swedish nested case-control study reported associations between certain HLA class II genotypes and viral load of specific oncogenic HPV types. 17,18 A Brazilian community-based cohort study showed that specific HLA class II haplotypes increased the risk of HPV persistence. 19 However, a Canadian cohort study of female university students found no associations between specific HLA class II alleles and risk of HPV persistence.…”
mentioning
confidence: 99%